Do Values Impact Development of Personality? A Critical Study on Young Adults - Mayurakshee Gangopadhyay (UIN Sunan Gunung Djati Bandung, 2022)
In an individual's life sense of right and wrong, chosing the correct alternatives and successful social participation are guided and directed by an internalized cognitive structure which is called values. As personality of an individual develops through constant interaction with the environment, values become an unavoidbale part of the process. The aim of the present study was to find out the impact of values on personality of young adults. 600 youth aged between 18 to 21 years was selected as sample. Personal Values Questionnaire by Sherry and Verma and Multi-dimensional Assessment of Personality by Sanjay Vohra and general information schedule were administered on the samples. The results indicate except religious value and family prestige value all other dimensions of values have positive correlation with the dimensions of personality. All the dimensions of personality are found out to be positively predicted by values.